1998
DOI: 10.2466/pms.1998.87.3f.1441
|View full text |Cite
|
Sign up to set email alerts
|

Realistic Expectations on the Putting Green: Within and between Days Trueness of Roll

Abstract: To improve putting performance, golfers have often used goal-setting techniques which require realistic performance expectations. Thus, examining whether external factors such as putting green irregularities affect putting performance is crucial to goal setting. The purpose of the study was to examine fluctuations in the trueness of roll of a golf ball across a green. A ball was mechanically rolled across a green in the morning and afternoon on a day when there was normal play and on a day when the course was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…A true surface can be described as one that is reliable, unfailing, or sure (http://Dictionary.com). Koslow and Wenos (1998), Baker and Spring (2010), and Windows (2011) described putting green trueness as the amount of lateral deviation a golf ball has from the desired line. In addition, Baker and Spring (2010) and Windows (2011) described smoothness as the amount of vertical deviation the ball has as it rolls across the surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A true surface can be described as one that is reliable, unfailing, or sure (http://Dictionary.com). Koslow and Wenos (1998), Baker and Spring (2010), and Windows (2011) described putting green trueness as the amount of lateral deviation a golf ball has from the desired line. In addition, Baker and Spring (2010) and Windows (2011) described smoothness as the amount of vertical deviation the ball has as it rolls across the surface.…”
mentioning
confidence: 99%
“…Unlike ball roll distance, very little scientific data has been published on trueness. Koslow and Wenos (1998) examined fluctuations in trueness across a golf green by measuring dispersion of a rolled ball as the lateral deviation from a straight line extended from a mechanical putting device to the resting point of the initial roll. They found the least amount of dispersion was in the morning.…”
mentioning
confidence: 99%
“…No peer‐reviewed research has evaluated the impact of annual bluegrass on ball roll directional imprecision. Koslow and Wenos (1998) used a mechanical putting machine to determine that the greatest ball roll distances, and the least amount of dispersion was present when fewer golfers traversed greens. David Pelz (2000) likewise described the area radially from 0.15 to 1.8 m around the golf cup as the “lumpy doughnut” due to golfer foot traffic that reportedly disturbed canopy characteristics and negatively affected putt direction.…”
Section: Resultsmentioning
confidence: 99%
“…Although the objective of a golf putt is both directionally and distally dependent, it is surprising that no to very little scientific data have been published that characterize the influence of putting green surfaces on ball roll direction. Koslow and Wenos (1998) evaluated fluctuations in ball roll trueness across a green using a mechanical putting machine and reported that trueness can vary on a golf green from day to day and within the same day depending on the time of day and traffic patterns. However, Koslow and Wenos (1998) did not assess the actual source of variation for trueness.…”
mentioning
confidence: 99%
See 1 more Smart Citation